Comparison of Glasgow coma scale, motor component, eye component, and simplified motor scale for predicting trauma outcomes: a 13-year multicenter retrospective cohort study - Shu-Jui Lee; Yu-Long Chen; Tsung-Hsien Wu; Chi-Yuan Liu; Chien-Hsing Wang; Chia-Hung Tsai; Jui-Yuan Chung; Giou-Teng Yiang; Meng-Yu Wu (BMC Emergency Medicine)
Abstract Background To address the complexity and time-consuming nature of the full Glasgow Coma Scale (GCS), various simplified tools for assessing brain function have been proposed, such as the eye (GCSE) and motor component of the GCS (GCSM), and the Simplified Motor scale (sMS). However, few studies have evaluated the predictive ability of these scoring systems. Methods A 13-year cohort study was conducted using the trauma database of Tzu Chi Hospital to compare the accuracy of the full GCS with those of the GCSE, GCSM, and sMS for predicting short- and long-term mortality (3-day mortality, 7-day mortality, and in-hospital mortality), intensive care unit (ICU) stay of ≥ 14 days, and hospital stay of ≥ 30 days in patients with trauma. Results This study included 41,297 patients with trauma. The full GCS achieved slightly higher area-under-the-receiver-operating-characteristic-curve (AUROC) values for predicting 3-day mortality (full GCS vs. GCSM vs. sMS: 0.899 vs. 0.894 vs. 0.890), 7-day mortality (0.871 vs. 0.864 vs. 0.861), in-hospital mortality (0.833 vs. 0.817 vs. 0.815), ICU length of stay (LOS)of ≥ 14 days (0.645 vs. 0.628 vs. 0.628), and hospital LOS of ≥ 30 days (0.607 vs. 0.587 vs. 0.587). The GCSE exhibited inferior discriminative ability for all clinical outcomes. The AUROC values for the ability of the sMS to predict 3-day mortality, 7-day mortality, and in-hospital mortality were comparable to those of the GCSM but lower than those of the full GCS for patients aged ≥ 65 years, aged < 65 years, with or without cardiovascular diseases, and with or without traumatic brain injury. For predicting ICU LOS of ≥ 14 days and hospital LOS of ≥ 30 days, the discriminative accuracy of the full GCS was marginally higher than those of the GCSE, GCSM, and sMS across the aforementioned subgroups. However, GCSE, GCSM, and sMS had similar discriminative accuracy. Conclusions Although the full GCS assessment exhibited higher accuracy in predicting 3-day mortality, 7-day mortality, in-hospital mortality, ICU LOS of ≥ 14 days, and hospital LOS of ≥ 30 days compared with the GCSE, GCSM, and sMS, the marginally higher accuracy of the full GCS may be negligible given its time-consuming nature. Furthermore, use of the GCSM provides no substantial advantage over use of the simpler sMS, which has comparable predictive accuracy. Clinical trial number Not applicable.